2007
DOI: 10.1176/appi.ajp.2007.06091479
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Aripiprazole on D 2 , 5-HT 2 , and 5-HT 1A Receptor Occupancy in Patients With Schizophrenia: A Triple Tracer PET Study

Abstract: Aripiprazole exhibits a unique occupancy profile as compared with other conventional and atypical antipsychotics. The threshold for response appears to be higher than 60%, extrapyramidal side effects appear to be uncommon even at occupancies that exceed the conventional extrapyramidal side effects threshold of 80%, and 5-HT(2) occupancy is lower than D(2) occupancy. Implications for aripiprazole's mechanism of action are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 224 publications
(147 citation statements)
references
References 31 publications
4
140
1
2
Order By: Relevance
“…receptors (-2-44%) at doses between 10 to 30 mg in schizophrenia patients. EPS was seen only in two of four subjects with D 2 occupancies exceeding 90% (Mamo et al, 2007). In accordance with the study of Bantick et al (2004), who showed that clozapine did not occupy the 5-HT 1A receptor at clinical doses, these data do not support an important role of the 5-HT 1A receptor regarding antipsychotic activity.…”
Section: Antipsychotic Drug Action and Serotonin Receptor Occupancysupporting
confidence: 86%
“…receptors (-2-44%) at doses between 10 to 30 mg in schizophrenia patients. EPS was seen only in two of four subjects with D 2 occupancies exceeding 90% (Mamo et al, 2007). In accordance with the study of Bantick et al (2004), who showed that clozapine did not occupy the 5-HT 1A receptor at clinical doses, these data do not support an important role of the 5-HT 1A receptor regarding antipsychotic activity.…”
Section: Antipsychotic Drug Action and Serotonin Receptor Occupancysupporting
confidence: 86%
“…PET studies are also consistent with the view that at clinically relevant doses, those agents, which are direct acting antagonists of D 2 receptors, have higher occupancy of D 2 than 5-HT 2A receptors (Goyer et al, 1996;Nyberg et al, 1999;Gefvert et al, 2001;Kessler et al, 2005). Aripiprazole, a partial D 2 receptor agonist, has a higher D 2 than 5-HT 2A receptor occupancy at clinical doses, but, nevertheless, has a weak functional effect to inhibit D 2 receptor stimulation (Mamo et al, 2007). As mentioned under Introduction, diminished dopaminergic and noradrenergic function in the cortex and HIP have been implicated in the pathophysiology of cognitive impairment, negative symptoms, and perhaps depression in patients with schizophrenia (Meltzer and McGurk, 1999;Millan, 2006;Juckel et al, 2006).…”
Section: Da Effluxsupporting
confidence: 70%
“…To elucidate this, further studies based on the same design using a selective antagonist for dopamine D 2 receptors, such as sulpiride, should be considered. In addition, a new antipsychotic drug aripiprazole that is a partial agonist to dopamine D 2 receptors has recently been used for treatment of schizophrenia (Mamo et al, 2007). Further studies to investigate the effects of aripiprazole on dopamine synthesis capacity should also be considered.…”
Section: Discussionmentioning
confidence: 99%